2006
DOI: 10.1115/1.2402181
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Localized Radial Basis Function Meshless Method for Fluid Flow and Conjugate Heat Transfer

Abstract: A localized radial basis function (RBF) meshless method is developed for coupled viscous fluid flow and convective heat transfer problems. The method is based on new localized radial-basis function (RBF) expansions using Hardy Multiquadrics for the sought-after unknowns. An efficient set of formulae are derived to compute the RBF interpolation in terms of vector products thus providing a substantial computational savings over traditional meshless methods. Moreover, the approach developed in this paper is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 27 publications
0
71
0
1
Order By: Relevance
“…It is often found that a higher valued shape parameter causing the interpolation matrix to become close to ill-conditioned gives the best accuracy [1,2]. The issue of the ill-conditioning does not allow for global interpolation as solutions are not accurate, but researchers have found that locally interpolating using RBF methods resolves these issues [2,4,7,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often found that a higher valued shape parameter causing the interpolation matrix to become close to ill-conditioned gives the best accuracy [1,2]. The issue of the ill-conditioning does not allow for global interpolation as solutions are not accurate, but researchers have found that locally interpolating using RBF methods resolves these issues [2,4,7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques originate from spectral methods based on Legendre or Chebyshev polynomial, which require uniform point distribution [8][9][10]. However, the meshless methods using radial basis functions (RBF) can be used on non-uniform distributions of points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localized RBF collocation meshless methods (LRC-MM) address the issues that arise from the global RBF approach, see [1,6]. LRC-MM have been implemented in the solution of incompressible fluid flows effectively adapting upwinding schemes for convective-dominated flows, see [1,3,5,6]. However, in decoupling the governing equations for incompressible fluid flows, a Poisson-like equation arises for the solution of the pressure field at each time step.…”
Section: Introductionmentioning
confidence: 99%
“…These are being used to resolve complex problems, such as flow transport problems, see [3]. There are several advantages to them such as accuracy control, since additional nodes made be added where needed, and a more accurate representation of the objects through meshfree discretization, see [4].…”
Section: Introductionmentioning
confidence: 99%